Colony Angmagssalik, Greenland. Postcard # 3 of the Danish Missionary Society : Kolonien Angmagssalik, Grønland. Postkort nr. 3 fra Det danske Missionsselskab - Buchhave, Th. (University of Southern California Digital Library (USC.DL), 2015)
Colony Angmagssalik, Greenland. Postcard # 3 of the Danish Missionary Society